Modulated Fluorescence in LB Films Based on DADQs—A Potential Sensing Surface? - Marek Szablewski; Richard L. Thompson; Lars-Olof Pålsson (Molecules, 2022)
Novel fluorescent Langmuir-Blodgett (LB) films have been constructed from three different amphiphilic dicynaoquinodimethanes (DADQs). The DADQs varied in functional group structure, which had an impact on the LB film structure and the fluorescence properties. As the fluorescence of DADQs competes with non-radiative decay (conformational change), the packing and/or free volume in the LB film will influence the average fluorescence lifetime and integrated intensity. The pristine (blank) LB films were then exposed to a selection of non-fluorescent target analytes (some with environmental relevance) and the fluorescence was measured and analyzed relative to the pristine LB film. Exposure of the LB films to selected target analytes results in a modulation of the fluorescence, both with respect to average fluorescence lifetime and integrated intensity. The modulation of the fluorescence is different for different DADQ LB films and can be attributed to restricted non-radiative decays or charge transfer reactions between target analyte and DADQ LB film. The response from the DADQ LB films shows that these systems can be developed into sensing surfaces based on fluorescence measurements.